Mechanisms of TLR4-Mediated Autophagy and Nitroxidative Stress - Zhang, Kunli; Huang, Qiuyan; Deng, Shoulong; Yang, Yecheng; Li, Jianhao; Wang, Sutian (Frontiers in Cellular and Infection Microbiology, 2021)
Pathogenic infections have badly affected public health and the development of the breeding industry. Billions of dollars are spent every year fighting against these pathogens. The immune cells of a host produce reactive oxygen species and reactive nitrogen species which promote the clearance of these microbes. In addition, autophagy, which is considered an effective method to promote the destruction of pathogens, is involved in pathological processes. As research continues, the interplay between autophagy and nitroxidative stress has become apparent. Autophagy is always intertwined with nitroxidative stress. Autophagy regulates nitroxidative stress to maintain homeostasis within an appropriate range. Intracellular oxidation, in turn, is a strong inducer of autophagy. Toll-like receptor 4 (TLR4) is a pattern recognition receptor mainly involved in the regulation of inflammation during infectious diseases. Several studies have suggested that TLR4 is also a key regulator of autophagy and nitroxidative stress. In this review, we describe the role of TLR4 in autophagy and oxidation, and focus on its function in influencing autophagy-nitroxidative stress interactions.